The impact of derivatives collateralisation on liquidity risk: Evidence from the investment fund sector - Audrius Jukonis; Elisa Letizia; Linda Rousová (European Central Bank (ECB), 2022)
Stricter derivative margin requirements have increased the demand for liquid collateral but euro area investment funds which use derivatives extensively have been reducing their liquid asset holdings. Using transaction-by-transaction derivatives data, we assess whether the current levels of funds' holdings of cash and other highly liquid assets would be adequate to meet funds' liquidity needs to cover variation margin calls on derivatives under a range of stress scenarios. The estimates suggest that between 13% and 33% of euro area funds with sizeable derivatives exposures may not have sufficient liquidity buffers to meet the calls. As a result, they are likely to redeem MMF shares, procyclically sell assets and draw on credit lines, thus amplifying the market dynamics under such stress scenarios. Our findings highlight the importance of further work to assess the potential role of macroprudential policies for non-banks, particularly regarding liquidity risk in funds.
Keywords: C60; G23; G13; G17; 330; variation margin; EMIR data; market stress; big data; non-bank financial intermediaries